The Teacher's Code of Ethics as a Foundation for Behavior in the Implementation of Christian Religious Education Learning in Schools - Deak, Victor; Chukwu, Shania (Jurnal Pendidikan Agama Kristen (JUPAK), 2024)
The teacher plays a strategic role in the educational process because the teacher contributes to the formation of student personalities. However, in the implementation of education, including Christian religious education in schools, educational problems related to teacher ethics were founded, therefore this code of ethics is needed as a guideline to regulate the actions and behavior of every educator. This research aims to explain the importance of a teacher's code of ethics as a basis for behavior to maintain teacher professionalism in implementing Christian religious education in schools. In this research, a qualitative research method was used with literature study as a tool to collect data and then present it descriptively. From this research, it can be concluded that the application of a teacher's code of ethics as a basis for behavior plays a central role in forming a learning environment with integrity and responsibility. Teachers who make the Code of Ethics a basis for behavior not only protect themselves from unethical or unprofessional actions but also maintain the trust of students, parents, and the community in educational institutions.